RIWAYAT HOSPITALISASI, KEHADIRAN ORANG TUA TERHADAP RESPON PERILAKU ANAK PRA SEKOLAH PADA TINDAKAN INVASIF: HISTORY OF HOSPITALIZATION, THE PRESENCE OF PARENTS IN PRE-SCHOOL CHILDREN’S BEHAVIORAL RESPONSES TO INVASIVE MEASURES - Sri Mulyani (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2018)
INTRODUCTION Children undergoing treatment at the hospital will experience anxiety and stress. One of the anxieties felt by pediatric patients when they have to get hospitalization is invasive action carried out by the health team. METHOD Analytical quantitative research design Cross sectional approach. The study was conducted in the Child Care Room Raden Mattaher Jambi Hospital in 2016 on September 5 to 21, 2016. The population of this study were all pre-school aged children who were treated in the Child Care Room at Raden Mattaher Hospital in Jambi in 2016 as many as 128 children.6 The number of samples was determined Purposively Sampling amounted to 30 respondents. The research instrument is an observation sheet. The instruments in this study have been tested for validity and reliability. Data analysis used univariate analysis and chi square test. RESULTS of 30 respondents who had been treated before were 8 respondents (26.7%), never treated as many as 22 respondents (73.3%). of 30 respondents who showed unfavorable behavioral responses as many as 14 respondents (46.7%) while respondents who showed good behavior responses were 16 (53.3%). out of 30 respondents who were not accompanied by parents, there were 11 respondents (36.7%), who were accompanied by parents, 20 respondents (63.3%). CONCLUSIONS AND SUGGESTIONS The results of the p-Value 0.012 statistical test concluded that there was a significant relationship between the history of hospitalization and the child's behavioral response. The statistical test results obtained by p-Value 0.001 concluded that there was a significant relationship between the presence of parents and the child's behavior response. The results of this study are expected to become information material for the hospital to be able to improve the quality of service in carrying out nursing care in pediatric patients who experience the impact of hospitalization Key words : Hospitalization History, Parent Presence, Behavior in Invasive Actions